2012
DOI: 10.1111/j.1600-0447.2011.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual exacerbation of schizophrenia symptoms

Abstract: Clinical recommendations• Clinicians treating women with schizophrenia need to inquire about menstrual exacerbation of symptoms.• The nature of the symptoms that are premenstrually exacerbated will determine the correct intervention.• Raising the dose of prolactin-raising antipsychotics can be counterproductive because estrogen levels can fall and ovulation can be inhibited. Additional comments• There are inherent safety risks to treatment with estrogens, but selective estrogen receptor modulators (SERMs) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 78 publications
0
33
0
5
Order By: Relevance
“…Some studies have also observed negative correlations between estradiol and visospatial abilities in women [206]. Sex steroid hormones have been also implicated in the pathophysiology of schizophrenia [58, [207][208][209].…”
Section: Sex Steroid Hormones and Neurocognitive Function In Schizophmentioning
confidence: 97%
“…Some studies have also observed negative correlations between estradiol and visospatial abilities in women [206]. Sex steroid hormones have been also implicated in the pathophysiology of schizophrenia [58, [207][208][209].…”
Section: Sex Steroid Hormones and Neurocognitive Function In Schizophmentioning
confidence: 97%
“…Functionally, estrogen may exert a neuroleptic effect by altering post-synaptic dopaminergic signal transduction and, consequently, inhibiting dopamine-mediated psychotic symptoms (Seeman, 2008). The estrogen hypothesis may explain, at least in part, the reduced early-onset and preponderance of late-onset schizophrenia in women (Seeman, 2012). Clinically, the estrogen hypothesis may also explain the greater psychotic symptomatology and worse neurocognitive performance in women after menopause and during low estrogen phases of menstruation (Seeman, 2012).…”
Section: Biological Differencesmentioning
confidence: 98%
“…The estrogen hypothesis may explain, at least in part, the reduced early-onset and preponderance of late-onset schizophrenia in women (Seeman, 2012). Clinically, the estrogen hypothesis may also explain the greater psychotic symptomatology and worse neurocognitive performance in women after menopause and during low estrogen phases of menstruation (Seeman, 2012). Cortisol has also been linked to gender differences, and Pruessner et al (2008) were the first to report that men -but not women -with recent onset psychosis experience blunted cortisol release, compared to healthy controls, after awakening: subsequent work found this was also true during mental challenges (Steen et al, 2011).…”
Section: Biological Differencesmentioning
confidence: 98%
“…Women suffering PMS are not only suffering from mental disease but also from fluid retention, edema in their ankles through increase of aldosterone [57]: Edema and aldosterone are always concomitantly increased in severe mental disease (Figure 7) [20]. Women suffering from PMS report suffering from anxiety, which is related to increased aldosterone [43].…”
Section: Dna Repair As Part Of Innate Immunity Response In Human Pregmentioning
confidence: 97%
“…Androstenediol stimulates innate immune cell function in nerve system cells and in healthy cells reduces DNA damage and induces genes that modulate genes related to the innate immunity in nerve cells [61]. It has been reported, in vitro, that in severe mental disease the formation of new healthy cells is inhibited and that the reduction of androstenediol is a key steroidal hormone promoting neurogenesis and a reduction may cause severe mental diseases [57,61,62].…”
Section: Dna Repair As Part Of Innate Immunity Response In Human Pregmentioning
confidence: 98%